Influence of the Work Units’ Psychological Ownership and Intention in Establishing the Patient Safety Program in Hospitals in Probolinggo, East Java - Mirrah Samiyah1 , Thinni Nurul Rochmah1 , Widodo J. Pudjihardjo1 , Usman Hadi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: There is high rate of patient safety incidents in the hospitals, which reaches 1217 incidents(21,31%) from 2016 until July 2017. There are some factors which cause the high rate of the patientsafety incidents which come from the hospitals. The aim of this research is to analyze the effects of thepsychological ownership and intention towards the work units’ output performance in carrying out thepatient safety program in the hospitals.Materials and Method: This research uses the survey research method with the cross-sectional approach. Itwas carried out from October 2018 until January 2019. The research samples are the service unit, supportingunit, management and general sector in the work units 4 hospital ini Probolinggo City, Indonesia. Thesamples are obtained using the simple random sampling method. The instruments used are questionnairesand observation sheets. The analysis is carried out using linear regression tests.Result: The work unit’s psychological ownership in carrying out the patients’ safety program is regarded asgood, with the rate of 46,7%. The work unit’s intention in carrying out the patients’ safety program is alsoregarded as good, with the rate of 41,1%. The work unit’s output in carrying out the patients’ safety programin Probolinggo Regency is regarded as bad, with the rate of 64,5%. There is a significant influence of thepsychological ownership variable (p-value=0,02) and intention (p-value=0,00) towards the output’s workperformance in carrying out the patients’ safety program in the hospitals of Probolinggo Regency.Conclusion: The work unit’s psychological ownership and intention have a significant effect towards thework unit’s work performance in in carrying out the patients’ safety program in the hospitals of ProbolinggoRegency on 2019. The hospitals should carry out work unit approaches instead of individual approaches toincrease the report of the patient safety incidents.